2015
DOI: 10.1017/s0007114515000574
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dietary starch to hepatic and systemic carbohydrate fluxes in European seabass (Dicentrarchus labraxL.)

Abstract: In the present study, the effects of partial substitution of dietary protein by digestible starch on endogenous glucose production were evaluated in European seabass (Dicentrarchus labrax). The fractional contribution of dietary carbohydrates v. gluconeogenesis to blood glucose appearance and hepatic glycogen synthesis was quantified in two groups of seabass fed with a diet containing 30 % digestible starch (DS) or without a carbohydrate supplement as the control (CTRL). Measurements were performed by transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
6
22
0
Order By: Relevance
“…Given that AAs, especially gluconeogenic AAs, can promote glucose production through hepatic gluconeogenic pathway (5, 15), we presume that both the elevated FAA levels and the reduced glycemia by rapamycin may be related to the suppressed hepatic gluconeogenesis, as previously demonstrated (16), implicating the importance of hepatic gluconeogenesis in modulating glucose homeostasis. Notably, consistent with this deduction, recent work using stable tracer method by Viegas et al (89) revealed that supplementation of digestible starch resulted in a significant reduction of gluconeogenic contributions to systemic glucose appearance in sea bass.…”
Section: High Carbohydrate Intake Induced Hyperglycemia Irrespective mentioning
confidence: 54%
“…Given that AAs, especially gluconeogenic AAs, can promote glucose production through hepatic gluconeogenic pathway (5, 15), we presume that both the elevated FAA levels and the reduced glycemia by rapamycin may be related to the suppressed hepatic gluconeogenesis, as previously demonstrated (16), implicating the importance of hepatic gluconeogenesis in modulating glucose homeostasis. Notably, consistent with this deduction, recent work using stable tracer method by Viegas et al (89) revealed that supplementation of digestible starch resulted in a significant reduction of gluconeogenic contributions to systemic glucose appearance in sea bass.…”
Section: High Carbohydrate Intake Induced Hyperglycemia Irrespective mentioning
confidence: 54%
“…In vitro studies, namely the infusion of adipocytes with 14 C-glucose (Bou et al, 2016) have also contributed to a better understanding this subject. Instead of following the metabolic fate of a single labeled substrate, the stable isotope deuterium ( 2 H), presented as deuterated water ( 2 H2O) in fish tanks, rapidly equilibrates with fish body water (Viegas et al, 2011) and gets widely incorporated in newly synthesized metabolites such as alanine (Marques et al, 2016), glucose or glycogen (Viegas et al, 2015). Similarly, 2 H gets incorporated into different sites of the triacylglycerol (TAG) molecule following well-defined metabolic steps from which estimations for de novo lipogenesis (DNL) and glycerol turnover can be derived (Viegas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We cannot discard that in addition to speciesspecificity, differences in the effect of starvation on the expression of Gdh among experiments may result also from diet composition, ration size and feeding regime. In this regard, it is well known that dietary protein greatly influences the hepatic activity of Gdh in fish (Liu et al 2012, Borges et al 2013, Caballero-Solares et al 2015, Viegas et al 2015, Coutinho et al 2016. Indeed, it was reported that starvation decreased or unaffected Gdh activity in the liver of starved Dicentrarchus labrax depending on dietary protein levels (Pérez-Jiménez et al 2007).…”
Section: Figurementioning
confidence: 99%
“…Dietary protein increases plasma free amino acids, which in turn enhances Gdh-dependent deamination and leads to higher rates of ammonia excretion. Dietary supplementation of glutamate downregulates Gdh mRNA levels and decreases reductive Gdh activity in the liver of Sparus aurata (Gómez-Requeni et al 2003, Caballero-Solares et al 2015 and reduces Gdh activity in Pagellus bogaraveo (Figueiredo-Silva et al 2010), while it increases in Oncorhynchus mykiss (Moyano et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation